Victoria, Queen of England : Scenes from Victoria Regina ... Retold by L.W. Taylor and E.C. Parnwell - Housman, Laurence 1865-1959. (London : Oxford University Press, 1942)
National Theatre, direction, A.L. Erlanger Realty Corporation, business management, S.E. Cochran, Gilbert Miller presents Helen Hayes in "Victoria Regina," by Laurence Housman, staged by Mr. Miller, entire production designed by Rex Whistler.
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: Victoria, -- Queen of Great Britain, -- 1819-1901 -- Drama; Theater programs -- Washington (D.C.); Theater programs -- 1935.